Analisis Makna Referensial Dan Dampak Slogan TerhadapPerilaku Peserta Didik Di Lingkungan Sekolah Menengah Pertama Negeri 2 Banyudono Kabupaten Boyolali - Susanto, Andis; , Dra. Atiqa Sabardila, M. Hum (2016)
he purposes of this study are (1) to identify the appropriate lingual unis on the slogan by clause. (2) to describe the use of referential meaning slogan in the SMP N 2 Banyudono. (3) to describe the opinion of the teachers and students of the slogans and influence the behavior of student. This study uses a qualitative method. The data in this research ere 30 slogans the contained within in the SMP N 2 Banyudono. Data collection techniques in this study using questionnaire, observation, and interviews. The validity of the data by triangulation. The data analysis method used is the method refrensial match. Results of the study are (1) slogans based on the clause, there are seven patterns clause: 10 slogans patterned Subject Predicate (SP), 4 slogan patterned Predicate Subject (PS), 4 slogans patterned Subject Predicate Description (SPK), 4 slogans patterned by Subject Predicate Complement (SP Pel), an explanation of the slogan of patterned Predicate (PK), a slogans patterned subject Predicate Object (SPO), and six slogans are phrases. (2) slogans based on the meaning of the type of meaning: there are six declarations slogans, representative there are nine slogans, there are three expressive slogans, there are eight slogans directive, and there are four commissive slogan. (3) there are 7 effect slogans that influences the behavior of learners is the slogans on the (5), (6), (9), (14), (24), (27) and (29). The results of this study are implemented as teaching materials in the teaching of writing text reviews at the Junior High School class VIII semester 2 on Competency Standards (12) to express information in the form of summaries, news text, and slogans/ posters. Basic Competence (12.3) Write a slogan/ poster for the purposes words and sentences variety, and persuasif. Keywords: slogans, referential meaning and influence of student behavior